Analysis of muscle synergy in the lower extremities and associated adaptive strategies during single-leg landing - Fu, Heyu; Yu, Dan; Chen, Yaru; He, Wenxiao; Duan, Yiting; Gao, Fan; Liu, Haibin (Frontiers in Physiology, 2025)
ObjectiveThis study aims to utilize OpenSim simulation technology to explore the muscle synergy in the lower extremities during single-leg landing and associated adaptive trategies.MethodsTwelve participants were recruited to perform single-leg landing tasks from various heights and distances. Kinematic and kinetic data were collected using the Vicon motion capture system, AMTI force platforms, and Noraxon electromyography system. Joint angles and muscle activations were computed using OpenSim.ResultsThe number of muscle synergy modules and the Variance Accounted For values showed high consistency across participants. Three muscle synergy modules were identified for landing tasks performed at 30 cm height with 0 cm and 30 cm horizontal distances, and at 45 cm height with 50 cm horizontal distance. Four modules were found for tasks performed at 30 cm height with 50 cm horizontal distance, and at 45 cm height with 0cm and 30 cm horizontal distances. The structure and activation timing of muscle synergy modules varied with changes in landing height and horizontal distance. Notably, the hip flexion angle significantly increased during the landing task at 30 cm height with 50 cm horizontal distance; the peak angles of the knee and ankle joints significantly increased at 45 cm height with 50 cm horizontal distance.ConclusionThe study demonstrates that structures and activation of muscle synergy vary with changes in landing height and horizontal distance, while showing high similarity in muscle synergy outcomes among participants. Moreover, landing height significantly affects the knee and ankle joints, while horizontal distance significantly influences the knee and hip joints.